CREATION OF FOREIGN LANGUAGE ATMOSPHERE IN TEACHING ENGLISH - Elena A. Veliyeva (International Journal of Innovative Technologies in Social Science, 2021)
During practical study it was offered a new model of the English language education for students, that was tested in current conditions of traditionally common at Azerbaijan national universities. The need to create this model is due to the dissatisfaction of the professional community with the results of such training. This paper consists of two parts. The first part briefly analyzes a number of interacting extralinguistic factors that differently influence the process of learning English by the students in the classrooms, in small training groups, under the guidance of the teacher according to standard methods. The second part of this paper is a description of the foreign language environment model in the single educational atmosphere of a technical university. The task set by the developers of this model is not only to reduce the negative and strengthen the positive influence of the external factors complex, but also to stimulate students for study of English through foreign-language socialization in academic and professionally oriented discourse. The principles of a model organization of the single foreign language atmosphere, a system of uniform control and assessment of English language proficiency are presented in this paper. Preliminary results obtained during the testing of this model were analyzed. The main advantages of the training organization through this model, which allows to increase motivation for students to learn English have been considered during the research.